Extensive Atraumatic Heterotopic Ossification of the Achilles Tendon in an Adolescent with Metabolic Syndrome: A Case Report. Issue 1 (January 2020) - Su, Lisa; Arshi, Armin; Beck, Jennifer J.
Abstract : Case: A 15-year-old boy with type 1 diabetes mellitus, hypertension, and obesity presented with atraumatic posterior ankle pain and stiffness due to extensive heterotopic ossification (HO) of the Achilles tendon. The ossification was successfully surgically resected and tendon primarily repaired. Wound dehiscence was noted at the first preoperative visit, managed conservatively by local wound care, and healed uneventfully by secondary intention. One-year follow-up showed no recurrence of HO, return to baseline activities, yet low Oxford scores. Conclusion: HO of the Achilles tendon is a rare clinical entity. We report an atraumatic case in an adolescent patient with metabolic syndrome, which may demonstrate systemic inflammation because of metabolic syndrome as a risk factor for HO.